RESILIENCE OF SOCIO-ECONOMIC SYSTEMS IN THE CONTEXT OF MODERN TURBULENCE AND ITS IMPACT ON ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS - PROKOPETS, Ruslan; KOROTYCH, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines topical issues concerning the functioning and development of socio-economic systems amidst increasing turbulence. It analyzes factors contributing to economic instability, such as global crises, geopolitical conflicts, and technological changes. Attention is also paid to the study of these systems’ resilience, their ability to adapt to challenges and maintain a trajectory of sustainable development. Theoretical and practical aspects of the impact of economic turbulence on the achievement of the Sustainable Development Goals are considered. The dynamics of the macroeconomic resilience index across world regions from 2007 to 2023 and forecast estimates of economic stability for the global economy and individual regions are analyzed. Analysis of available data indicates that modern socio-economic systems operate under conditions of heightened turbulence, driven by a complex set of interconnected factors. Among these, global economic crises, political instability, technological changes, and environmental challenges stand out. This turbulence significantly impacts the ability of economies and societies to ensure stable development and achieve the Sustainable Development Goals. Research into the resilience of socio-economic systems is becoming critically important. Resilience is considered not only as the ability to withstand external shocks but also as the capacity to adapt to changes while preserving key functions and the development trajectory. The effectiveness of economic policies aimed at ensuring sustainable development is closely linked to the economy’s ability to maintain macroeconomic stability and adapt to changing conditions. Assessing macroeconomic stability requires a comprehensive approach that considers a wide range of macroeconomic indicators, including economic growth rates, inflation, unemployment levels, the balance of payments, and others. The analysis of social aspects, such as the level of inequality, social cohesion, and access to education and healthcare, is also important. The development of interdisciplinary approaches to the analysis and management of socio-economic systems, integrating knowledge from economics, sociology, ecology, and other sciences, is crucial. This will allow for a more comprehensive understanding of the complex interrelationships between economic, social, and environmental processes and the development of more effective sustainable development strategies.